2019
DOI: 10.1126/sciadv.aau8857
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induction in atrophic muscle cells requires ULK1 activation by TRIM32 through unanchored K63-linked polyubiquitin chains

Abstract: Optimal autophagic activity is crucial to maintain muscle integrity, with either reduced or excessive levels leading to specific myopathies. LGMD2H is a muscle dystrophy caused by mutations in the ubiquitin ligase TRIM32, whose function in muscles remains not fully understood. Here, we show that TRIM32 is required for the induction of muscle autophagy in atrophic conditions using both in vitro and in vivo mouse models. Trim32 inhibition results in a defective autophagy response to muscle atrophy, associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 65 publications
1
67
0
Order By: Relevance
“…Further studies with TRIM5 showed that it also interacted with ATG14L1 and AMBRA1, both proteins that interact with the Beclin 1 complex. Additional studies have broadened the list of TRIMs that interact with the ULK1 and/or Beclin 1 complexes to include TRIMs 13, 16, 20, 21, 28, 32, and 50 (Yang et al, 2013;Kimura et al, 2015;Chauhan et al, 2016;Fusco et al, 2018;Di Rienzo et al, 2019;Ji et al, 2019). However, the finding that a TRIM interacts with these upstream regulators of autophagy does not necessarily prove that it acts to promote autophagy, as exemplified by TRIM17 which binds to ULK1 and Beclin 1 yet was found to inhibit autophagosome formation (Mandell et al, 2014;Mandell et al, 2016).…”
Section: Actions Of Trims On Autophagy Machinerymentioning
confidence: 99%
“…Further studies with TRIM5 showed that it also interacted with ATG14L1 and AMBRA1, both proteins that interact with the Beclin 1 complex. Additional studies have broadened the list of TRIMs that interact with the ULK1 and/or Beclin 1 complexes to include TRIMs 13, 16, 20, 21, 28, 32, and 50 (Yang et al, 2013;Kimura et al, 2015;Chauhan et al, 2016;Fusco et al, 2018;Di Rienzo et al, 2019;Ji et al, 2019). However, the finding that a TRIM interacts with these upstream regulators of autophagy does not necessarily prove that it acts to promote autophagy, as exemplified by TRIM17 which binds to ULK1 and Beclin 1 yet was found to inhibit autophagosome formation (Mandell et al, 2014;Mandell et al, 2016).…”
Section: Actions Of Trims On Autophagy Machinerymentioning
confidence: 99%
“…Knockdown cells were produced by transfecting Hek293T packaging cells with the lentiviral pLKO vector together with the Pax2 (pMDLg/p and pRSV-Rev plasmids) and ENV (VSV-G) plasmids [17]. The pLKO vector containing a shRNA for Prdx6 or for GFP (used as control), were purchased from Sigma Aldrich, Saint Louis, MO, USA.…”
Section: Stably Silenced Murine Myoblast C2c12 Cell Linementioning
confidence: 99%
“…This is particularly important under nutrient-deprived or stress conditions to maintain adequate energy production. Recent studies have shown that basal autophagy is crucial for the maintenance of muscle physiology, and that a maladaptive autophagy is implicated in various muscle diseases, including muscular dystrophy, sarcopenia, and myofibril degeneration [31,66,[82][83][84].…”
Section: Musclementioning
confidence: 99%